Determinants of the IDX BUMN20 Stock Index on the Indonesia Stock Exchange (A Macroeconomic Approach) - Elisa Elisa; Muhammad Rachmad R; Rahma Nurjanah (Jurnal Prajaiswara, 2026)
Introduction/Main Objectives: This study aims to analyze the effects of interest rates, exchange rates, world oil prices, and inflation on the IDX BUMN20 during the 2019–2024 period. The IDX BUMN20 represents state-owned enterprise (SOE) stocks that play a strategic role in the national economy and, in recent years, have shown relatively lagging performance compared to the Composite Stock Price Index. Background Problems: The performance gap between the IDX BUMN20 and the Composite Stock Price Index indicates differences in sensitivity to macroeconomic dynamics, making it important to examine the short-run and long-run effects of macroeconomic variables on the index. Research Methods: The study uses monthly secondary time series data from 2019–2024 obtained from the Indonesia Stock Exchange, Bank Indonesia, Statistics Indonesia, and the Federal Reserve Bank of St. Louis. The data are analyzed using the Autoregressive Distributed Lag (ARDL) model. Finding/Results: In the long run, the IDX BUMN20, interest rates, and world oil prices tend to have positive effects, while the exchange rate tends to have a negative effect in the initial period and inflation appears relatively weak. In the short run, the effects of the variables are dynamic and vary across lags. Conclusion: The findings confirm that the performance of state-owned enterprises (SOEs), as reflected in the IDX BUMN20, is strongly influenced by macroeconomic conditions. Therefore, strengthening corporate governance, managing exchange rate and financing risks, and ensuring policy stability are essential to sustain the strategic role of SOEs as development agents and contributors to government revenue.